2020
DOI: 10.1007/s13300-020-00898-8
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 and SARS-CoV-2 Infection: Might GLP-1 Receptor Agonists Play a Role?

Abstract: Recently it has been hypothesized that DPP4 inhibitors can have a beneficial effect on SARS-CoV-2 infection through immunoregulating activity.Experimental study on streptozotocintreated rats showed that liraglutide was able to stimulate the expression of pulmonary angiotensin converting enzyme 2 (ACE2) and angiotensin (1-7).Liraglutide modulated different elements of the renin angiotensin system (RAS), significantly increasing ACE2 and Mas receptor (MasR) mRNA expression in pup lungs from food-restricted mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…Indeed, several studies have reported protective associations between the use of GLP-1 RA and respiratory function [31][32][33] and risk of infections. 34 Second, it is also possible that the observed protective association is the result of an increased risk of pneumonia with DPP-4i. However, although there may be a biological mechanism linking DPP-4i to an increased risk of infections, [35][36][37] most previous studies of the pneumonia risk of DPP-4i did not identify an increased risk, [21][22][23][24][25]38 suggesting that this is an unlikely explanation for the observed association.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have reported protective associations between the use of GLP-1 RA and respiratory function [31][32][33] and risk of infections. 34 Second, it is also possible that the observed protective association is the result of an increased risk of pneumonia with DPP-4i. However, although there may be a biological mechanism linking DPP-4i to an increased risk of infections, [35][36][37] most previous studies of the pneumonia risk of DPP-4i did not identify an increased risk, [21][22][23][24][25]38 suggesting that this is an unlikely explanation for the observed association.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, GLP-1 receptor agonists have been associated with increased ACE2 expression in lungs and heart tissue and with beneficial effects in acute lung injury, with suggestions of possible helpful and harmful effects in COVID-19. 8,9 Recent studies have suggested a lower risk of COVID-19-related hospital mortality in people with type 2 diabetes who were prescribed metformin before hospital admission 10 or sitagliptin on admission. 11 Notwithstanding calls for ongoing scrutiny to understand the use, risks, and benefits of individual classes of glucoselowering drugs in people with type 2 diabetes and COVID-19, there are no comprehensive, comparative data on differential effects of glucose-lowering drugs on risk for severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Similarly, GLP-1 receptor agonists have been associated with increased ACE2 expression in lungs and heart tissue and with beneficial effects in acute lung injury, with suggestions of possible helpful and harmful effects in COVID-19. 8 , 9 Recent studies have suggested a lower risk of COVID-19-related hospital mortality in people with type 2 diabetes who were prescribed metformin before hospital admission 10 or sitagliptin on admission. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Besides being important glucose‐lowering agents, GLP‐1RAs pose promising anti‐inflammatory and anti‐obesogenic properties, pulmonary protective effects, as well as beneficial impact on gut microbiome composition. In conclusion, taking everything previously mentioned into consideration, GLP‐1RAs seem to be potential candidates for the treatment of patients, affected by COVID‐19 infection, with or even without type 2 diabetes mellitus, as well as excellent antidiabetic (glucose‐lowering) agents during COVID‐19 pandemic times 70 . Last but not least, it is of high importance to constantly evaluate new scientific data/evidence regarding pharmacotherapy in COVID‐19 pandemic times, based on evidence‐based medicine principles.…”
Section: Discussionmentioning
confidence: 81%